DESAIN SISTEM INFORMASI PENDAFTARAN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH SLEMAN - Sustin Farlinda; Siti Nurhidayah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractRegional General Hospital of Sleman have used the Hospital Management Information System. Hospitalinformation systems Sleman using Lazaruz as an application program, the database used is MySql databasein 2008, has been integrated to all services, including medical records system, billing system, pharmacy,radiology, laboratory and medical rehabilitation. Medical record information system consists of a system ofoutpatient registration, registration of inpatient, emergency room registration system, filling system, coding, andreporting hospital. However, because the hospital wanted to develop the Information System in Internal untilit is not depend on outsiders then make the resulting information system design based on the needs analysisand system flowcharts to obtain registration information system design models Outpatient Hospital of Slemannamely Context diagram Data Flow Diagram Level 1, Level 2 Data Flow Diagram, DataFlow Diagram Level 3 and Entity Relationship Diagram (ERD).Keywords: Hospital Information System Management, System Flowchart, Data Flow DiagramsAbstrakRumah Sakit Umum Daerah (RSUD) Sleman telah menggunakan Sistem Informasi Manajemen Rumah Sakit.Sistem informasi RSUD Sleman menggunakan Lazaruz sebagai program aplikasi, database yang digunakanadalah database MySql 2008, telah terintegrasi keseluruh pelayanan, meliputi sistem rekam Medis, sistembilling, farmasi, radiologi, laboratorium dan rehabilitasi medis. Sistem Informasi rekam medis terdiri darisistem pendaftaran rawat jalan, pendaftaran rawat inap, sistem pendaftaran IGD, sistem filling, coding, danpelaporan rumah sakit. Akan tetapi karena pihak Rumah Sakit ingin mengembangkan Sistem Informasitersebut secara Internal sehinnga tidak tergantung pada pihak luar maka di buat desain sistem informasi yangdihasilkan berdasarkan analisis kebutuhan dan flowchart sistem sehingga didapatkan model desain sistemInformasi Pendaftaran Rawat Jalan RSUD Sleman yaitu Context diagram Data Flow Diagram Level 1 , DataFlow Diagram Level 2 , Data Flow Diagram Level 3 dan juga Entity Relationship Diagram (ERD)Kata kunci: Sistem Informasi Manajemen Rumah Sakit, Flowchart Sistem, Data Flow Diagram